Community Involvement and Sustainable Wetland Conservation in Ruhama County Ntngamo District. - Nankunda, Emmanuel (Kabale University, 2024)
This study explored the impact of community involvement on sustainable wetland conservation in Ruhama County, Ntungamo District. The objectives included assessing community activities related to wetlands, examining conservation practices, and establishing the relationship between these activities and conservation efforts. A cross-sectional study design was employed, utilizing questionnaires and interviews for data collection. Findings revealed that most respondents indicated that cultivation occurs in the wetlands, while fewer mentioned activities such as firewood collection and fishing in swamps. Regarding wetland conservation practices, the most commonly cited practice was the enforcement of wetland regulations, while fewer respondents noted the involvement of local communities in conservation initiatives. The study also found a strong positive relationship between community activities and wetland conservation practices in Ruhama County. Based on these findings, the study recommended the establishment of local conservation groups to monitor wetland health, report illegal activities, and promote conservation education and advocacy. Additionally, it suggested providing training and support for community members on conservation techniques, including wetland monitoring, habitat restoration, and sustainable resource management.